Effectiveness of change from suvorexant to lemborexant drug in the treatment of sleep disorders. Issue 5 (10th June 2022) - Okino, Kazumaro; Suzuki, Hirohisa; Kondo, Seiji; Tomioka, Hiroi; Tokumasu, Takahiro; Yamada, Hiroki; Iwanami, Akira; Inamoto, Atsuko
Abstract : Background: This study aimed to examine the effects of a change in medication from suvorexant to lemborexant among patients with insomnia. Methods: Patients with chronic insomnia who had persistent insomnia for 3 months or longer and who had been taking suvorexant for 3 months or longer were selected. The participants were divided into two groups: the 'modified' group and the 'non‐modified' group. Four sub‐types of insomnia (i.e., difficulty initiating sleep, difficulty maintaining sleep, early‐morning awakening, and non‐restorative sleep) were investigated. Logistic regression was used to investigate improvements in both the groups after 12 weeks. Results: Among the 77 participants, 43 and 34 patients were in the modified drug group and the non‐modified drug group, respectively. Comparing sleep disorders between the two groups, we found significant improvement after 12 weeks in the modified drug group in terms of difficulty initiating sleep, compared with the non‐modified drug group (odds ratio = 0.036, P = 0.008, 95% CI = 0.003–0.415). However, no significant differences were found between the two groups in terms of difficulty maintaining sleep, early‐morning awakening, and non‐restorative sleep. Conclusions: Sleep disorders can be treated by alleviating difficulties in initiating sleep by changing from suvorexant to lemborexant. In addition, it was confirmed that the drug change caused no serious side effects and that it was highly safe and tolerated.